Prolonged exposure to arsenic in UK private water supplies: toenail, hair and drinking water concentrations. Issue 5 (27th April 2016) - Middleton, D. R. S.; Watts, M. J.; Hamilton, E. M.; Fletcher, T.; Leonardi, G. S.; Close, R. M.; Exley, K. S.; Crabbe, H.; Polya, D. A.
Abstract : Chronic exposure to arsenic (As) in drinking water is an established cause of cancer and other adverse health effects. Abstract : Chronic exposure to arsenic (As) in drinking water is an established cause of cancer and other adverse health effects. Arsenic concentrations >10 μg L −1 were previously measured in 5% of private water supplies (PWS) in Cornwall, UK. The present study investigated prolongued exposure to As by measuring biomarkers in hair and toenail samples from 212 volunteers and repeated measurements of As in drinking water from 127 households served by PWS. Strong positive Pearson correlations ( r p = 0.95) indicated stability of water As concentrations over the time period investigated (up to 31 months). Drinking water As concentrations were positively correlated with toenail ( r p = 0.53) and hair ( r p = 0.38) As concentrations – indicative of prolonged exposure. Analysis of washing procedure solutions provided strong evidence of the effective removal of exogenous As from toenail samples. Significantly higher As concentrations were measured in hair samples from males and smokers and As concentrations in toenails were negatively associated with age. A positive association between seafood consumption and toenail As and a negative association between home-grown vegetable consumption and hair As was observed for volunteers exposed to <1 As μg L −1 in drinking water. These findings have important implications regarding the interpretation of toenail and hair biomarkers. Substantial variation in biomarker As concentrations remained unaccounted for, with soil and dust exposure as possible explanations.